Acute flexor tendon injury following midshaft radius and ulna fractures in a paediatric patient. (June 2018) - Williams, James; Wharton, Rupert; Peev, Peter; Horwitz, Maxim
Abstract: Delayed rupture of the extensor and flexor tendons are recognised complications of distal radius fractures. However, acute flexor tendon rupture in the context of forearm fractures is rare. A twelve-year-old female sustained midshaft fractures of the radius and ulna. Intra-operatively the flexor pollicis longus (FPL) was found to be stripped from its musculotendinous junction at the level of the fracture fragment. The ruptured tendon was repaired using a modified Krackow technique at the time of fracture fixation. The repair was protected in plaster of Paris prior to referral to the paediatric hand clinic. The patient made a full recovery. Flexor tendon injury is a rare but potentially devastating consequence of acute forearm fractures. High energy trauma, significant volar angulation of the fracture fragment and clinical signs of flexor tendon injury should raise suspicion of this injury. A high index of suspicion in conjunction with repeat clinical examination of flexor tendon function should be performed before opting for closed management or intramedullary nailing in paediatric patients.